PERILAKU KONSUMSI SUSU CAIR MASYARAKAT DI DAERAH PERKOTAAN DAN PEDESAAN (MILK CONSUMPTION BEHAVIOR OF URBAN AND RURAL COMMUNITIES) - Wahyu Dyah Prastiwi; Hery Setiyawan (Department of Agribusiness, Faculty of Agriculture, Universitas Trunojoyo Madura, Indonesi, 2016)
The relationship between socio-economic factors, preference, and comparison of fluid milk consumption behavior between urban and rural consumers were explored in this study. The respondents were housewives or adult family member who responsible for food shopping. Respondents had positive perception of product characteristics and attributes. Socio-economic variables namely income, education level and family size found significantly have relationship with fluid milk consumption behavior. Product characteristics and attributes found significantly correlated with fluid milk consumption behavior. This research found highly significant difference (p0.01) of fluid milk consumption behavior between urban and rural respondents. This paper underlined that fluid milk producers should maintain the continuity and quality of their products. The government should improve their role in the mechanism of controlling and supervising the quality of fluid milk and give guarantee in the stability of price and equal distribution in all urban and rural areas.